Letter to the Editor: Is Golf the New Football or Have We Made It So? - Deora, Harsh; Yagnick, Nishant S; Tripathi, Manjul; Mohindra, Sandeep (Sports Medicine International Open, 2019)
Lumbar Spine Injuries: Primary Prevention in Amateur and Professional Golf PlayersSir,We read with interest the article by Goebel et al. 1 (Goebel D, Drollinger F, Drollinger A. Lumbar Spine Injuries: Primary Prevention in Amateur and Professional Golf Players. Sports Med Int Open. 2018; 2:179–184). We have been deeply interested in this sport and delved on the musings of competitiveness causing athletes to put un-natural strains on their bodies and vice-versa. While we do understand the cause of Lumbar spine injuries caused by athletes putting undue stress on their bodies, we need to understand that the reason for the same.